One RLC: Building a strong and unified sales culture from a decade of disparity - Cootauco, Ma. Mercedes (Animo Repository, 2021)
This Insider Action Research unified the culture of the Sales Department of Robinsons Land Residential Division, aligned the purpose with the revised value proposition of the new brand, and ensured that a servant leadership culture is fostered and sustained for the years to come. Culture in the workplace has always played an important role in the growth and success of businesses. Some may focus on building a winning culture in the workplace while some may focus on other matters that they see more important such as improving productivity. Sometimes, fostering the right culture is unintentionally put to the side when all that matters is the level of productivity. When the priority is the output, the journey along the way sometimes becomes irrelevant. To ensure a comprehensive and impartial action research, I used different tools such as ORJI framework, Ladder of Inference, Meta-learning, Force Field Analysis, Types of Inquiry, and Sustainability Framework, and more. These tools guided me all throughout the two cycles. The first cycle of the research ensured that it reached its audience all at the same time through including it in the program of the new brand’s Internal Launch, which my department and I organized. The Culture Building was injected into the program so that it aligned with the new brand’s propositions and the discussion of the transition was seamless. Second cycle was implemented through a more focused approach wherein the Training Department and I collaborated to come up with a comprehensive plan for culture-building to be used in their series of training.